2021
DOI: 10.1111/geb.13420
|View full text |Cite
|
Sign up to set email alerts
|

Does island ontogeny dictate the accumulation of both species richness and functional diversity?

Abstract: Aim:The accumulation of functional diversity in communities is poorly understood.Conveniently, the general dynamic model of island biogeography (GDM) makes predictions for how such diversity might accumulate over time. In this multiscale study of land snail communities on 10 oceanic archipelagos located in various regions of the globe, we test hypotheses of community assembly in systems where islands serve as chronosequences along island ontogeny.Location: Ten volcanic archipelagos. Time period:From 23 Ma to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 96 publications
2
10
1
Order By: Relevance
“…As independent variables, this study used island area, elevation, the average distance from the surrounding landmasses and the changing rate of effective population sizes (Appendix 5; Table S6). Although previous studies have demonstrated that island age affects the species richness and functional diversity of land snails (Kraemer et al, 2022; Parent & Crespi, 2006), we did not use island age because the Izu Islands are relatively young (Tani et al, 2011) and detailed geological data are unknown. The species phylogeny with the estimated divergence times was converted to a variance–covariance matrix using the ‘ape’ library on R (Paradis & Schliep, 2019; R Core Team, 2022) and added to our model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As independent variables, this study used island area, elevation, the average distance from the surrounding landmasses and the changing rate of effective population sizes (Appendix 5; Table S6). Although previous studies have demonstrated that island age affects the species richness and functional diversity of land snails (Kraemer et al, 2022; Parent & Crespi, 2006), we did not use island age because the Izu Islands are relatively young (Tani et al, 2011) and detailed geological data are unknown. The species phylogeny with the estimated divergence times was converted to a variance–covariance matrix using the ‘ape’ library on R (Paradis & Schliep, 2019; R Core Team, 2022) and added to our model.…”
Section: Methodsmentioning
confidence: 99%
“…The second variable was island elevation. Similar to island areas, elevation is also expected to increase environmental heterogeneity and contribute to species richness (Chiba et al, 2009;Parent & Crespi, 2006) and phenotypic diversity of the snail community (Kraemer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, our research team is particularly interested in exploring biodiversity in native land snails in South America (Parent and Crespi, 2006;Phillips et al, 2020;Kraemer et al, 2021). Globally, snails possess extraordinary diversity and high levels of endemism, and represent 70% of mollusk extinctions.…”
Section: Species' Characterizationmentioning
confidence: 99%
“…After their complete emergence, islands are transformed by erosion processes, which causes a reduction in topographical complexity and habitat diversity affecting the rate of immigration, speciation and species extinction (Fernández-Palacios de Nascimento et al 2011, Whittaker et al 2007). As a result, lower richness should occur on the newly formed as well as on the sinking and eroding late stage islands, whereas higher richness is expected in the middle-stage islands (Kraemer et al 2022, Whittaker et al 2017, Whittaker et al 2008. Likewise, endemism rate should decrease with the increase in extinction resulting from ontogenetic changes (Chen andHe 2009, Whittaker et al 2007).…”
Section: Introductionmentioning
confidence: 99%